The blind side [videorecording] - Netter, Gil. (Burbank, CA Warner Home Video, 2010)
Michael Oher is a homeless African-American teenager who is from a broken home. Mike is taken in by the Touhys, a well-to-do white family who help him fulfill his potential. At the same time, Oher?s presence in the Touhys? lives leads them to some insightful self-discoveries of their own. Living in his new environment, Mike faces a completely different set of challenges to overcome-- as both a football player and student. Mike works hard and, with the help of his coaches and adopted family, becomes an All-American offensive left tackle.
Sandra Bullock, Tim McGraw, Quinton Aaron, Jae Head, Lily Collins, Ray McKinnon, Kim Dickens, Adriane Lenox, Kathy Bates.
Keywords: Families -- Drama; Homeless teenagers -- Tennessee -- Drama; African American football players -- Tennessee -- Drama; Football -- Offense -- Tennessee -- Drama